In vitro benchtop mock circulatory loop for heart failure with preserved ejection fraction emulation - Malone, Andrew; Gallagher, Sean; Saidi, Jemil; Rizq, Gina; O’Dowd, Enda; Vallence, Derek; Hameed, Aamir (Frontiers in Cardiovascular Medicine, 2022)
In this work, a novel mock circulatory loop (MCL) is presented that is capable of simulating both healthy cardiac function and Heart Failure with preserved Ejection Fraction (HFpEF). This MCL differs from others presented in the literature as it features two independently actuated heart chambers, representing the left atrium and the left ventricle. This is an important improvement over other designs as it allows for potential HFpEF treatments to be examined, not just in relation to their effect on the left ventricle but also on the left atrium. The aim of this work was to show that novel MCL designs could be developed to allow for testing of new mechanical circulatory support devices for the treatment of HFpEF. Two loop configurations are presented, one featuring hard PVC cylindrical chambers and one that features soft silicone chambers which are anatomically analogous to the native heart. We show that both MCLs are capable of simulating the onset of HFpEF with a sustained increase in diastolic pressure of 62.03% and a sustained decrease in end diastolic volume (EDV) of 14.24%.